Evidence associated with the metabolic effect of carbohydrate restriction in patients with type II diabetes mellitus: An integrative literature review (Research, Society and Development, 2022)
Type 2 Diabetes Mellitus (DM2) is one of the non-communicable pathologies that have a high prevalence, incidence in Brazil and in the world, and may be related to the development of cardiovascular diseases and other comorbidities. Evidence suggests that dietary management based on carbohydrate restriction has significant effects on the course of the disease, given that it is a nutrient that has the greatest impact on postprandial blood glucose. The aim of the study was to highlight the metabolic effects that carbohydrate restriction provides in individuals with type II diabetes mellitus. This is an integrative literature review carried out in the Virtual Health Library (VHL) and PubMed. Controlled and randomized clinical trials published in the last 6 years in English were prioritized, among the exclusion criteria, all studies that did not approach the selected methodology in question. The following Health Sciences Descriptors (DeCS) were used: “carbohydrate-restricted diet”, “type 2 diabetes mellitus” and diet, for this purpose, the Boolean operator “AND” was used. The results indicate that a low-carbohydrate diet results in a decrease in cardiometabolic indicators, such as: better control of metabolic parameters related to glycemic and lipid profiles, greater predisposition to reduce anthropometric measurements and less need for hypoglycemic drugs. Therefore, it is concluded that the dietary approach is fundamental in the treatment and prevention of this disorder, especially when based on carbohydrate restriction.